2022
DOI: 10.3389/fgene.2022.996310
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a focal adhesion signaling pathway-related ceRNA network in pelvic organ prolapse by transcriptome analysis

Abstract: Objective: Pelvic organ prolapse (POP) affects a large proportion of adult women, but the pathogenesis of POP remains unclear. The increase in global population aging will impose a substantial medical burden. Herein, we aimed to explore the related RNAs regulating the occurrence of POP and provide potential therapeutic targets.Method: Tissue biopsies were collected from the anterior vaginal wall of six women with POP and six matched subjects without POP. The profiles of mRNAs, circRNAs, lncRNAs, and miRNAs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Focal adhesion is the close-fitting linking between the cell and the extracellular matrix that allows their communication and signaling [98]. It includes a complex of junctional sign proteins that introduce the actin cytoskeleton to the integrins, and it controls several cellular processes like relocation, proliferation, distinction, apoptosis, and gene expression [99]. According to the focal adhesion sensitivity to mechanical forces, it regulates its construction and role [100].…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion is the close-fitting linking between the cell and the extracellular matrix that allows their communication and signaling [98]. It includes a complex of junctional sign proteins that introduce the actin cytoskeleton to the integrins, and it controls several cellular processes like relocation, proliferation, distinction, apoptosis, and gene expression [99]. According to the focal adhesion sensitivity to mechanical forces, it regulates its construction and role [100].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ECM2 can be used as a prognostic biomarker for low-grade gliomas, and high ECM2 expression promotes glioma proliferation, migration, and invasion ( 55 , 56 ). PPP1R12B is involved in the regulation of cell-matrix adhesion dynamics and traction force turnover ( 57 , 58 ). EMILIN1, an adhesive ECM glycoprotein, forms stable intra-chain salt bridges with α4β1 integrins, which enhance cell adhesion ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion of POP-HVFs to the ECM was decreased, resulting in impaired tissue morphology at the microstructural level. In terms of cellular morphology, a separate study revealed severe disruption of fibroblast cytoskeletal actin filaments in fibroblasts from POP patients, suggesting a close association between abnormalities in this cellular support protein and external mechanical stretching ( 24 ). Besides, increasing evidence suggests that the vaginal microbiome and the immune system are closely linked to maintain a healthy vaginal environment and lower genitourinary health ( 25 ).…”
Section: Pop and Biomechanicsmentioning
confidence: 99%